Psychopathology of organic brain disorders - Calderón, Jorge; Toro, Pablo (Frontiers in Psychiatry, 2024)
The concept of mental symptom is constructed considering not only the biological signal that determines it, but the multilayered causative factors related to intersubjective experience. However, specific brain damage might produce a set of symptoms expressed in a recognizable gestalt that helps to differentiate organic of psychogenic causation. The legacy of the theory of mental symptoms developed by German Berrios and the seminal work of Hughlings Jackson and Kurt Goldstein can contribute to this difficult task.